What's your diagnosis? A rare cutaneous benign tumor - Ana G. Lopes; Maria J. Guimarães; Catarina Cerqueira; Joana Gomes; Celeste Brito (Revista da Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Our case focuses on a 30-year-old female patient with no relevant priors.